2014
DOI: 10.4102/koedoe.v56i1.1214
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ perceptions and willingness to pay for the control of <i>Opuntia stricta</i> invasion in protected areas: A case study from South Africa

Abstract: Invasive alien plants have a long history of establishment in the national parks of South Africa.In particular, Opuntia stricta (sour prickly pear) has invaded several protected areas in thecountry, threatening the biodiversity conservation mandate of these conservation areas. Thisarticle focuses on the economic estimation of O. stricta’s negative impacts in protected areas byusing Contingent Valuation surveys conducted amongst a sample of tourists in the PilanesbergNational Park (North West Parks and Tourism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Visitors also appear willing to support spending money on these activities. Other studies [ 29 , 30 ] have shown park visitors are willing themselves to financially support the control of invasive species through park entry fees, and/or indirectly via taxes that are then used to fund park and weed management. Although not assessed here, some visitors may also be willing to directly participate in weed reduction strategies such as volunteering for trail maintenance and restoration events [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visitors also appear willing to support spending money on these activities. Other studies [ 29 , 30 ] have shown park visitors are willing themselves to financially support the control of invasive species through park entry fees, and/or indirectly via taxes that are then used to fund park and weed management. Although not assessed here, some visitors may also be willing to directly participate in weed reduction strategies such as volunteering for trail maintenance and restoration events [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result public support for park management in general and for weed management in particular, is important [ 26 28 ]. Visitors often financially support weed management in parks directly via the payment of park fees, and/or indirectly via taxes that are subsequently used for park management [ 29 , 30 ]. Support could potentially include changes in behaviour so visitors are unlikely to carry and disperse weed seeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amount Willing to Pay for social tree services for the conservation of tree species. The elicited monetary values of social services of tree species were obtained through the Payment Card System (CPS) of Contingent Valuation Method (CVM) as used by [21] and [26]. The students were asked to indicate the maximum amount they will be WTP per month for social services provided by the tree species from their allowances.…”
Section: Willingness To Pay For Trees Socialmentioning
confidence: 99%
“…This is similar for attitudes towards non-native ornamental species that are found in rest camps in Kruger National Park (Foxcroft, Richardson & Wilson 2008), where it required education and increased awareness of staff to gain support for the removal of such plants. Similarly, tourists in Pilanesberg who were aware of the invasive prickly pear (Opuntia stricta) indicated a willingness to contribute financially to its control (Nikodinoska et al 2014). In an 'open-access' scenario such as the GRNP where visitors do not necessarily have to pass through a gate to experience the park, the demarcation between PAs, surrounding buffer zones and the rest of the landscape is less easily observable.…”
Section: Synthesis Of Insightsmentioning
confidence: 99%